THE WHILTON DISPUTE, 1264-1380 : A Social-Legal Study of Dispute Settlement in Medieval England - Robert C. Palmer (Princeton University Press, 2014)
THIS BOOK is designed to serve as a teaching tool, as a researcher's guide, and as a scholarly investigation. The latter two purposes need little explanation. The book takes the form of a case study that puts litigation into a familial, social, and societal context. The material on which it is based is perhaps uniquely suited for such a task in this area. As a guide, the book will enable researchers to hypothesize better the kind of material that might be found to supplement nonlegal material or to fill out an isolated entry in a plea roll, as well as to piece together the kind of social reality that lies behind the often seemingly sterile record of a single lawsuit. The book's intended use as a teaching tool, however, has shaped the format. There is little written in legal history that is accessible to nonspecialists, and nothing that discusses the law of property in a properly social instead of a doctrinal framework. The discussion here thus begins at a very basic level. Moreover, numerous documents have been provided in translation, many incorporated into the text and others in the appendixes. The placement of documents in the text is the result of my belief that familiarity with the documents themselves is necessary for an understanding of the subject. The text provides a general overview, but it also assumes that the reader will undertake a close analysis of the documents, for each one raises fundamental legal issues that will demand and repay close consideration and discussion. Furthermore, enough statutory material has been provided in Appendix 2 both to support problems raised in the text and to illustrate the difficulties of statutory interpretation. Notes have been kept to an absolute minimum and have not been used for bibliographic purposes. For such purposes recourse may be had to S.F.C. Milsom, Historical Foundations of the Common Law, 2nded. (London, 1981), and John Baker, An Introduction to English Legal History, 2nd ed. (London, 1979).